(untitled) (Global Business Management Review (GBMR), 2020)
Pakistan ranks third in the list of the most hazardous countries for woman’s survival. In this study, by using the quantitative approach, the scale adaptation process was conducted in three phases as integration of instruments, generation of items, and generalization of expert reviews. Back-to-Back translation on 40 women was done to determine the understanding of the Urdu language of personal empowerment scale. Sequentially, Confirmatory Factor Analysis (CFA) was performed on the data collected from 360 respondents for the Construct Validity Method (CVM) on personal empowerment Scale-Urdu Version. The results confirmed the validity of the scale. Cross-language validity was also determined. The empirical findings also indicated that women’s personal empowerment plays a significant role in improving their quality of life. Theorists and practitioners need to pay more attention to the generalization of the personal empower scale.